Peningkatan Leukosit, Neutrofil, dan Prokalsitonin Persisten Tanpa Bukti Infeksi pada Kanker Stadium Akhir: Sebuah Laporan Kasus - Yanuar, Santosa; Ahani, Ardhi Rahman; Setiabakti, Andrian; Rizka, Aulia; Sinto, Robert (Jurnal Penyakit Dalam Indonesia, 2024)
Elevation of leukocyte, neutrophil, and procalcitonin (PCT) has been known as a marker of bacterial infection independent of the underlying disease. This article will describe a case of end-stage cancer with persistent elevation of leukocyte, neutrophil, and procalcitonin with no evidence of infection. A 45-year-old female presented with abdominal distension for three months prior to hospital admission. The patient was suspected to have breast cancer with hepatic metastasis based on diagnostic tests. Throughout treatment, the patient experienced persistent elevation of leukocytes, neutrophils, and PCT despite no signs or symptoms of infection from history, physical examination, and diagnostic tests. The patient received antibiotic therapy including ciprofloxacin escalated to meropenem, but leukocytes, neutrophils, and PCT did not decrease. A breast tumor biopsy was performed. The result of biopsy revealed after the patient had passed away. The histopathology was invasive carcinoma, No Special Type (NST) of right breast. The immunohistochemistry showed luminal B type, HER2 positive. The persistent increase in leukocytes and neutrophils in this patient indicates poor prognosis, disease progression, metastasis, and pro-cancer activity of neutrophils. The elevated PCT in this patient may be due to systemic inflammation and/or aberrant secretion from the cancer itself.